2017
DOI: 10.18203/2320-1770.ijrcog20172923
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury requiring dialysis in obstetric patients: management and clinical outcome in case series of 30 patients in a tertiary care centre

Abstract: Background: Acute Kidney Injury is a common medical problem affecting approximately 5% of all hospitalized and 30% of critically ill patients. The incidence in obstetric patients ranges from 1 in 2000 to 1 in 25000 pregnancies. In India till date, the impact of AKI on fetomaternal outcome and pertaining therapeutic interventions is only sparsely studied.Methods: It is a retrospective cross-sectional study. All obstetric patients with AKI on dialysis, admitted to Shree Krishna Hospital, a tertiary care hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…2 Previously, it was assumed that AKI is reversible but recent epidemiological evidence has shown that even mild AKI has important clinical implications and is associated with future risk for hypertension, cardiovascular diseases and even death. [3][4][5] Also, AKI is a major driver for chronic kidney disease (CKD), and CKD is the sixth fastestgrowing cause of death.…”
Section: Introductionmentioning
confidence: 99%
“…2 Previously, it was assumed that AKI is reversible but recent epidemiological evidence has shown that even mild AKI has important clinical implications and is associated with future risk for hypertension, cardiovascular diseases and even death. [3][4][5] Also, AKI is a major driver for chronic kidney disease (CKD), and CKD is the sixth fastestgrowing cause of death.…”
Section: Introductionmentioning
confidence: 99%